Growth and Productivity of Chironomus sp. in Enriched Substrat by Chicken Manure 1,0-2,5 g/l - D. Shafruddin; B.R. Parlinggoman; K. Sumantadinata (Jurnal Akuakultur Indonesia)
Chironomus sp. larvae or called as bloom worm contains high nutrient and caroten that are important to support fish and shellfish culture, especially ornamental fishes.  Larval Chironomus is abundant in environment rich of organic and inorganic compounds. This study was carried out to examine growth and productivity of Chironomus larvae reared in water containing 1.0, 1.5, 2.0 and 2.5 g of chicken manure per liter water.   The growth of chironomus larvae for 4 weeks rearing was reached a peak at the third week. Higher population, 19,680 larvas, was obtained by the highest dose of fertilizer.  Growth by length and weight of Chironomus larvae of all treatments was similar